Effects of the Irrigation Management Programme on Boro Rice Productivity and Agrarian Income Inequality In North-West Bangladesh - Arif, Md. Taufiqul (1991)

(untitled)
Rice is the staple food of the people of Bangladesh. The importance of rice in the country's social,economic and political life cannot be overemphasized; yet the country has food grain deficit. Boro rice is mainly grown in modern varieties (MV) during the winter season under full-scale irrigation. The existing irrigation facilities and the winter cropping intensity together offer good scope f or expanding the cultivation of boro rice which may lead to food grain self-sufficiency. However, a large number of installed deep tubewells (DTW) are reportedly not being utilized properly in the north-western part of the country. It is claimed that a majority of the marginal and small farmers have been deprived of these irrigation facilities by the small minority of the large farmers. Present trend indicates a decrease in foodgrain productivity and an increase in agrarian income inequality. The landless population is ever-increasing and poverty is spreading steadily. An Irrigation Management Programme (IMP) is introduced to increase the foodgrain productivity, and reduce the agrarian income inequality. This should expand the DTW command area, and encourage the marginal and small farmers in boro rice growing activities. It is important to assess whether IMP has increased the boro rice productivity and reduced the income inequality. For this purpose, two models are used, one to analyze the boro rice productivity, and another to measure the agrarian income inequality. The former is a log-linear Cobb Douglas (LCD) regression model, while the latter comprises Theil's first and second entropy measures. Fourteen explanatory variables are used in the productivity model, land, labour, capital and management being the major ones. The management variable is directly measured as a composite of the social, economic and technological factors influencing scheme management performance levels. The inequality models are used to measure both inter-scheme and intra-scheme income inequality arising from the net boro rice income, all other incomes, and the total income. The results indicate that IMP has significantly contributed to increasing the boro rice productivity and the overall. resource use efficiency, but it has not been able to change the significantly income inequality. The IMP schemes have significantly larger command area and better management performance level than the non-IMPs. Because of IMP, the inequality within the privileged groups has decreased, but that within the underprivileged has increased. The group size of the owner-cum-tenants is likely to be squeezed. However,the IMP is expected to increase the demand for labour, causing their wage rate to increase. All different groups will have more income. The land-rich will be richer, but the poor might not become poorer. This is likely to improve the overall living standard in the rural society.